2022
DOI: 10.1038/s41598-022-25687-0
|View full text |Cite
|
Sign up to set email alerts
|

Soil qualities and change rules of Eucalyptus grandis × Eucalyptus urophylla plantation with different slash disposals

Abstract: Slash disposal changes soil quality by affecting soil properties and nutrient cycling, and the appropriate disposal approaches remain controversial. This work aimed to explore the impact of different slash disposal methods on soil qualities. For this purpose, a Eucalyptus grandis × Eucalyptus urophylla plantation that had been cultivated in 2002 and felled for the third time in 2016 was established in Hezhou City, China. Burning forest (BF, for moderate intensity fire) and no-burning forest (NF) were set in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…Zhao et al showed that the soil porosity and water-holding capacity of Eucalyptus plantations with a continuous application of nitrogen fertilizer decreased by 10.3%~17.1% and 9.4%~15.0% [25], respectively. In this study, although there was almost no significant difference in the soil physical properties between the inorganic fertilizer group and the organic fertilizer group, the application of inorganic fertilizer still increased soil BD and reduced soil porosity and MWC, while the organic fertilizer relatively improved soil pore structure, which was similar to the previous research results [26,27].…”
Section: Effects Of Fertilization On Soil Physical and Chemical Prope...supporting
confidence: 89%
“…Zhao et al showed that the soil porosity and water-holding capacity of Eucalyptus plantations with a continuous application of nitrogen fertilizer decreased by 10.3%~17.1% and 9.4%~15.0% [25], respectively. In this study, although there was almost no significant difference in the soil physical properties between the inorganic fertilizer group and the organic fertilizer group, the application of inorganic fertilizer still increased soil BD and reduced soil porosity and MWC, while the organic fertilizer relatively improved soil pore structure, which was similar to the previous research results [26,27].…”
Section: Effects Of Fertilization On Soil Physical and Chemical Prope...supporting
confidence: 89%
“…to the weight of water in the same volume (Zhang et al, 2022). The specific gravity test was carried out to determine the specific gravity of liquid soap.…”
Section: Specific Weight Testmentioning
confidence: 99%